2014
DOI: 10.3390/app4030402
|View full text |Cite
|
Sign up to set email alerts
|

Towards Laser Driven Hadron Cancer Radiotherapy: A Review of Progress

Abstract: It has been known for about sixty years that proton and heavy ion therapy is a very powerful radiation procedure for treating tumors. It has an innate ability to irradiate tumors with greater doses and spatial selectivity compared with electron and photon therapy and, hence, is a tissue sparing procedure. For more than twenty years, powerful lasers have generated high energy beams of protons and heavy ions and it has, therefore, frequently been speculated that lasers could be used as an alternative to radiofre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 124 publications
(177 reference statements)
0
75
0
1
Order By: Relevance
“…More importantly, the radiobiological effectiveness of these beams needs must be assessed. For they exhibit unprecedented spatio-temporal physical features [7]. The physical pattern of the energy deposition events at nanometric scale and their subsequent very early stage (10 -12 -10 -6 s) radiochemical evolution determines the biological outcome, shaping the role of biochemical repair processes [8].…”
Section: The Rationale For Laser-driven Cancer Hadrontherapymentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the radiobiological effectiveness of these beams needs must be assessed. For they exhibit unprecedented spatio-temporal physical features [7]. The physical pattern of the energy deposition events at nanometric scale and their subsequent very early stage (10 -12 -10 -6 s) radiochemical evolution determines the biological outcome, shaping the role of biochemical repair processes [8].…”
Section: The Rationale For Laser-driven Cancer Hadrontherapymentioning
confidence: 99%
“…several orders of magnitude larger than the ones used in the current therapeutic regimes [9]. While laser-driven particle beams can be thus seen as a valuable probe to investigate the core mechanisms of radiation action at the sub-nanometer and femtosecond scales [10,11], it has been suggested that the extreme spatio-temporal nature of laser-driven particle beams may ensue unknown biological responses [7,12,13]. Hence, ultra-fast high-energy particle radiobiology will have to ascertain whether and to what extent cellular radiosensitivity is influenced by such peculiar irradiation regimes.…”
Section: The Rationale For Laser-driven Cancer Hadrontherapymentioning
confidence: 99%
“…The present authors strongly believe that the emergence of charged particle therapy from basic and fundamental research is a boon to those with cancer problems to improve their quality of life, and will also be highly useful for non-cancer diseases in future. A statement about the prohibitive cost of hadron beam therapy is worth recollecting 35 : 'Although most developing countries would find the costs required for a conventional accelerator-based hadron therapy center to be prohibitive, they might find a laser-based system to be more affordable given national budgets. These countries could potentially afford 5-10 million € to initiate a laser-driven beam center that can guide future innovation.…”
Section: Discussionmentioning
confidence: 99%
“…A strong motivation for the field of laser-driven ion acceleration is the prospective of future application to cancer therapy [20], and the potential advantages of laser-accelerated ions were reviewed in the talk by C. Obcemea (Memorial Sloan Kettering Cancer Center, New York).…”
Section: Beam Transport Manipulation and Applicationsmentioning
confidence: 99%